2011
DOI: 10.1007/s11069-011-9900-y
|View full text |Cite
|
Sign up to set email alerts
|

Parameter estimations of a storm surge model using a genetic algorithm

Abstract: A genetic algorithm was used to optimize the parameters of the two-dimensional Storm Surge/Tide Operational Model (STORM) to improve sea level predictions of storm surges. The model was then tested using data from Typhoon Maemi, which landed on the Korean Peninsula in 2003. The following model parameters were used: the coefficients for bottom drag, background horizontal diffusivity, Smagorinsky's horizontal viscosity, and sea level pressure scaling. The simulation results using the optimized parameters improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…If the weight does not provide the optimal solution, the algorithm continues to the next generation through operators such as crossover, mutation, and replacement until an optimal solution is obtained (Henao, 2011). Here, the minimum RMSE between observation and model anomalies is used as the fitness function (Lee et al ., 2006; You et al ., 2012; Ahn and Lee, 2016). Ahn and Lee (2016) showed that the MME method applying GA to both single‐model and MME improved the performance for both winter temperature and precipitation, even over higher‐latitude land areas, compared to conventional SCM.…”
Section: Methodsmentioning
confidence: 99%
“…If the weight does not provide the optimal solution, the algorithm continues to the next generation through operators such as crossover, mutation, and replacement until an optimal solution is obtained (Henao, 2011). Here, the minimum RMSE between observation and model anomalies is used as the fitness function (Lee et al ., 2006; You et al ., 2012; Ahn and Lee, 2016). Ahn and Lee (2016) showed that the MME method applying GA to both single‐model and MME improved the performance for both winter temperature and precipitation, even over higher‐latitude land areas, compared to conventional SCM.…”
Section: Methodsmentioning
confidence: 99%
“…The fitness function used in this study is the minimum root‐mean‐square error (RMSE) between observation and hindcast anomalies. RMSE, which is a simple and effective fitness function, has been used by several previous studies [e.g., Lee et al ., ; You et al ., ]. RMSE is defined as follows: RMSE=1Ttruetrue∑j=1TkjOj2 kj=truetrue∑i=1N()Ai,italicj×wi where T and N are the total number of time and input data, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…This method extends the skillful ENSO forecast from 6 leading months to 12 leading months. Parameter adjustment, also known as parameter estimation or optimization, is commonly used to reduce the model errors [9][10][11][12][13][14]. Parameter adjustment automatically finds the optimal parameter values by assimilating observations over a period, to make the simulations approach the observations as much as possible [15].…”
Section: Introductionmentioning
confidence: 99%